ESTUDO TEÓRICO E EXPERIMENTAL DA TRANSESTERIFICAÇÃO DO ÓLEO DE BABAÇU COM ÁLCOOL α-BISABOLOL - NASCIMENTO, Wellington da Conceição Lobato do (2022)
This work presents a study of the transesterification reaction of babassu oil with α- bisabolol, which is an unsaturated monocyclic tertiary alcohol. In the theoretical study, the semi-empirical PM6 method (Parametric Method 6) and the DFT (B3LYP) method (Density Functional Theory) were used for the uncatalyzed esterification and transesterification reactions and the DFT (B3LYP), HF-3c and DFT (M062X 6- 31+G(d,p)) for the catalyzed esterification and transesterification reactions. The methodology consisted of optimizing the structures of the molecules to obtain energetic parameters such as: dipole moment vectors, electrostatic potential map (MESP), infrared spectroscopy, energy of the HOMO and LUMO molecular orbitals. By thermodynamic calculations, ∆H0, ∆G0 and ∆S0 of the uncatalyzed reactions were obtained. The transition energies of the uncatalyzed reactions were obtained by the DFT method (B3LYP). The results of the computational calculations showed that both the esterification reaction and the transesterification reaction do not occur spontaneously without the presence of catalysts. Regarding the calculations of the catalyzed reactions, the results showed that the energies obtained tend to spontaneity of these reactions when applied heterogeneous catalysts. In the experimental part, the catalysts Al2O3, CeO2 and Al2O3/CeO2(5%) were obtained and characterized using the techniques of Scanning Electron Microscopy with Energy Dispersive X-Ray (SEM - EDS) and Fourier Transform Infrared Spectroscopy (FTIR). The transesterification reactions were carried out in a 100 mL round-bottomed glass flask, using a heating control plate and a mechanical stirrer. The reaction mixture (oil, α-bisabolol alcohol and catalyst) was kept under constant stirring, with a speed of 1250 rpm. The analyzes of the composition of the esters were carried out in a Gas Chromatograph coupled to a Mass Spectrometer (GC-MS). The results showed that the catalyst Al2O3/CeO2(5%) showed better catalytic activity for conversion to esters.